2015
DOI: 10.3109/07357907.2015.1009631
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Cancer: Frequently Asked Questions When Guidelines are Inconclusive

Abstract: Management of Venous thromboembolism (VTE) in cancer patients is difficult when guidelines are inconclusive. To share a reasonable and homogeneous behavior in such circumstances, four issues, which are felt as problematic by oncologists and surgeons, have been selected; all were uncovered or only partially covered by current guidelines. Results from the literature and author's specific experience in the field were utilized to suggest reasonable solutions to the raised questions. The reported experience is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…This has been possible because a center for the diagnosis and treatment of PE is active at the University Hospital, where patients are followed according to a standard clinical strategy. [31] Other authors reported results on patients followed for years after the discontinuation of 3 to 6 months of prophylaxis [3,8,27,30] or treated for a longer period of time but following a nonstandardized protocol. [30] Recently, a standardized, prospective study reported results on patients with unprovoked PE systematically treated for 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…This has been possible because a center for the diagnosis and treatment of PE is active at the University Hospital, where patients are followed according to a standard clinical strategy. [31] Other authors reported results on patients followed for years after the discontinuation of 3 to 6 months of prophylaxis [3,8,27,30] or treated for a longer period of time but following a nonstandardized protocol. [30] Recently, a standardized, prospective study reported results on patients with unprovoked PE systematically treated for 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The difference did not reach statistical significance; furthermore, the number of cancer related deaths was very small (8/199 in the control group and 4/197 in the screening group); these data, together with the physical and emotional discomfort for the patients related to the very demanding screening program, and with the cost of the program, suggest that extensive screening for cancer is not routinely warranted in patients with VTE. An approach based on individual characteristics that emerge after the initial history, physical examination, routine blood tests, and chest X-ray is for example what we recommend in patients admitted to our ward (22).…”
Section: Screening For Occult Cancer After An Episode Of Vtementioning
confidence: 99%
“…Because of the dependency of tumor growth to thrombosis, coagulation factors could be considered as a major risk factor in tumorigenesis [3,4]. Several studies have investigated the role of thrombosis factors in tumors and have shown the importance of thrombosis management in tumor treatment [5,6]. Although the coincidence of myoma and thrombosis is reported in several types of research [7,8], published studies on the association between myoma and thrombosisrelated mutations are limited.…”
Section: Introductionmentioning
confidence: 99%